Análisis de los resultados generados a partir de la modelación hidráulica de 3.5 km del Caño Usivar del municipio de Yopal, departamento de Casanare en el sofware HEC RAS 5.0.5 1D y 2D (2018)
The Hydraulic Modeling of surface water sources allows us to know, through hydrological and physical data of the basin, its behavior for different return periods, facilitating the planning of the territories. In this document, a characterization of the area direct and indirect influence of the project is made, more specifically of the Caño Usivar, in the neighborhood of the City of Yopal. Next, a hydrological analysis of the Caño Usivar basin is developed based on statistical analysis and HEC - HMS modeling. Next, the one-dimensional and two-dimensional HEC RAS modeling of the Caño Usivar is carried out, using the topographic information of the study area, acquired as secondary information for the development of the related project. Finally, the analysis of the results obtained in the modeling is presented.